A controllable exfoliation and in-situ conversion method for MXene

By grinding the MAX phase Ti3AlC2 and CuBr2, calcining in an argon atmosphere, and magnetically stirring with a weak oxidant at room temperature, the single-step controlled peeling and in-situ conversion of MXene is achieved, solving the problems of cumbersome and harsh conditions in the existing methods, reducing production costs and improving efficiency.

CN116534896BActive Publication Date: 2025-04-11SOUTHEAST UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310349665.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-04-11
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

The existing MXene oxidation methods are cumbersome and harsh, resulting in high production costs and low efficiency.

Method used

After grinding with MAX phase Ti3AlC2 and CuBr2 at a molar ratio of 1:5 to 7, it was calcined in an argon atmosphere, and then mixed with a weak oxidant and stirred magnetically at room temperature to achieve controlled peeling and in-situ conversion of MXene.

Benefits of technology

The single-step controlled peeling and in-situ conversion of MXene is realized, reducing production costs, improving production efficiency, and retaining the layered structure of MXene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116534896B_ABST
    Figure CN116534896B_ABST
Patent Text Reader

Abstract

The present invention discloses a controllable exfoliation and in-situ conversion method of MXene, comprising the following steps: step 1, converting MAX phase Ti 3 AlC 2 , CuBr 2 The mixture is fully ground and mixed in a molar ratio of 1:5-7, and transferred to a container; Step 2, the mixture obtained in Step 1 is calcined at 600-660°C in a protective atmosphere, and taken out after cooling to obtain m-Ti 3 C 2 T z , where z is Br; Step 3, m‑Ti 3 C 2 T z and a weak oxidant in a ratio of 1-2 g: 100 mL, and react under magnetic stirring at room temperature; Step 4, collecting and drying the product obtained in Step 3 to obtain amorphous TiO 2 @C. The present invention can achieve controlled exfoliation and in-situ conversion of MXene in just one step, without the complicated steps in traditional methods, which can effectively improve production efficiency; it does not require ice bath conditions, argon protection, and strict regulation of oxygen additives, which can effectively reduce production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a MXene conversion method, in particular to a controllable exfoliation and in-situ conversion method of MXene. Background Art

[0002] MXene is a new type of two-dimensional material, and its chemical expression can be expressed as n+1 X n T z , where M is a transition metal, X is carbon or nitrogen, T is a surface functional group (-OH, -O, -F, etc.), and n = 1, 2, 3, 4. Theoretical predictions show that there are more than 100 types of MXene, with very rich structural and component tunability. Therefore, MXene is an ideal platform material for the preparation of other two-dimensional materials.

[0003] The common method of oxidizing MXene mainly includes two steps: Step 1, peeling off the multi-layer MXene into a few-layer / single-layer MXene; Step 2, oxidizing the d-MXene under certain conditions. In step 1: The common method of peeling off MXene is generally to peel off m-MXene in an argon atmosphere in an ice bath ultrasound for a long time, which has high cost and low production efficiency. In step 2: Taking advantage of the sensitivity of d-MXene to oxygen, the appropriate oxidation conditions are adjusted for oxidation. The raw materials and oxidation conditions required in this step are relatively harsh and the steps are cumbersome. Improper operation will result in a product with a larger particle size, and it is difficult to retain the morphology of d-MXene, which leads to poor performance in subsequent applications.

[0004] The Chinese patent application number 202210570308.4 discloses a few-layer TiO2-MXene composite material, its preparation method and application, and uses concentrated hydrochloric acid to locally oxidize d-MXene colloid under hydrothermal conditions to obtain a method for in-situ growth of granular TiO2 nanocrystals on MXene. In the implementation of this patent, it is necessary to first ultrasonically and centrifugally treat m-MXene and collect the upper turbid liquid to obtain a thin layer of MXene colloid, and the preliminary preparation work is cumbersome. And it is necessary to use concentrated hydrochloric acid to locally oxidize MXene under hydrothermal conditions. The experimental conditions are dangerous and require more harsh conditions to obtain nanocrystalline TiO2. For example, the Chinese patent application number 202211088213.5 discloses a copper-based composite material strengthening method using MXene local in-situ oxidation to form a pinning effect with the matrix, and uses MXene local in-situ oxidation to generate oxide particles. Class "nail plate" structure reinforcement material, prepare MXene-class "nail plate" structure reinforcement-copper composite materials. The implementation of this patent requires ultrasonic stratification and centrifugation of m-MXene to obtain a MXene colloidal solution. Copper powder is mixed with the d-MXene colloidal solution and dried to obtain a mixed powder. The dried mixed powder is sintered under vacuum conditions using plasma discharge, and the MXene is locally oxidized in situ during sintering to generate nano-oxide particles. The implementation of this patent also requires the use of d-MXene for in-situ conversion, and also involves plasma discharge sintering. Although MXene can be oxidized, its process is cumbersome and the conditions are harsh.

[0005] In summary, the current methods for oxidizing MXene are relatively cumbersome and require harsh conditions. Therefore, it is necessary to develop a simple and low-cost method to achieve the purpose of controllable exfoliation and in-situ conversion of MXene, so as to reduce production costs and improve production efficiency. Summary of the invention

[0006] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for the controlled exfoliation and in-situ conversion of MXene with high production efficiency, low cost, simplicity and convenience.

[0007] Technical solution: The controllable exfoliation and in-situ conversion method of MXene described in the present invention comprises the following steps:

[0008] Step 1: Grind and mix MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:5-7 and transfer them into a container;

[0009] Step 2: calcining the product obtained in step 1 at 600-660°C in a protective atmosphere, cooling it down and taking it out to obtain m-Ti3C2T z , where z is Br, m means multilayer, T means terminal, and z means surface functional group;

[0010] Step 3: m-Ti3C2T z Mix with a weak oxidant at a ratio of 1-2 g to 100 mL and react under magnetic stirring at room temperature;

[0011] Step 4: collect and dry the product obtained in step 3 to obtain amorphous TiO2@C.

[0012] Furthermore, in step 1, the container is a crucible.

[0013] Furthermore, in step 2, the temperature is raised to 600-660°C at a heating rate of 3-5°C / min and kept at that temperature for 5-7h. The temperature is first lowered to 190-200°C at a rate of 8-10°C / min and then cooled in the furnace. The protective atmosphere is argon.

[0014] Furthermore, in step 3, the weak oxidant is ammonium persulfate solution (APS) or FeCl3 solution. The concentration of the weak oxidant is 0.5M to 2M. The speed of magnetic stirring is 500 to 700 rpm, and the time is 8 to 9 hours.

[0015] Furthermore, in step 4, the collection is performed by centrifugation or suction filtration. The drying is any one of vacuum drying, freeze drying, and natural drying, and the vacuum drying temperature is 75-85°C.

[0016] Furthermore, the specific surface area of ​​amorphous TiO2@C is 130-160 m 2 / g. The mass percentage of TiO2 is 30-35wt%, and the mass percentage of C is 65-70wt%.

[0017] Preparation principle: During the reaction, the solute molecules in the solution transform m-Ti3C2Br2 in situ and enter the interlayer space to cause the interlayer to expand, thereby increasing the interlayer spacing and damaging the interlayer space, thus achieving the result of controllable exfoliation of m-Ti3C2Br2.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0019] 1. Controllable exfoliation and in-situ conversion of MXene can be achieved in just one step, without the complicated steps in traditional methods, which can effectively improve production efficiency and can be applied to energy storage;

[0020] 2. No ice bath conditions, argon protection, or strict regulation of oxygen additives are required. The in-situ conversion of MXene can be completed at room temperature and in air atmosphere, which can effectively reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1is the XRD pattern of amorphous TiO2@C obtained in Example 1 of the present invention;

[0022] Figure 2 is a SEM image of amorphous TiO2@C obtained in Example 1 of the present invention;

[0023] Figure 3 is the XRD pattern of amorphous TiO2@C obtained in Example 2 of the present invention;

[0024] Figure 4 This is a SEM image of the amorphous TiO2@C obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0025] In the following examples, the average particle size of MAX phase Ti3AlC2 is 200-400 mesh, and the purity is ≥90wt%. CuBr2, McLean, AR 99%. m-Ti3C2T z In the above example, m means multi-layer, T z The meaning of is the surface functional group Br.

[0026] Example 1

[0027] A method for controlled exfoliation and in-situ conversion of MXene, comprising the following steps:

[0028] a. Grind MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:6 in a mortar for 20 min to fully mix the powders and transfer them to a corundum crucible, wherein Ti3AlC2 is 2 g;

[0029] b. The crucible of step a was transferred to a tubular furnace, and the temperature was raised to 600°C at a heating rate of 5°C / min under an argon atmosphere, and kept at this temperature for 6 hours. After the end of the heat preservation, the temperature was first lowered to 200°C at a rate of 10°C / min, and then cooled with the furnace to obtain m-Ti3C2T z ;

[0030] c. The m-Ti3C2T obtained in step b z The mixture was mixed with a 0.5 M weak oxidant ammonium persulfate solution at a ratio of 1 g:100 mL, and reacted at room temperature with magnetic stirring at 700 rpm for 8 h;

[0031] d. The solution obtained in step c was centrifuged at 8000 rpm for 3 min, and was centrifuged and washed twice with deionized water and anhydrous ethanol at 8000 rpm for 3 min each, the precipitate was collected and vacuum dried at 80° C. After collecting the powder, amorphous TiO2@C was obtained.

[0032] The specific surface area of ​​the amorphous TiO2@C obtained in this example is 137.4168 m 2 / g. The mass percentage of TiO2 is 30.33%, and the mass percentage of C is 69.67%.

[0033] like Figure 1 In the XRD spectrum of the amorphous TiO2@C obtained in this example, the small bulge at 20° to 30° corresponds to amorphous carbon, and there is no obvious diffraction peak in the figure, thus achieving the purpose of in-situ conversion of m-MXene.

[0034] like Figure 2 The amorphous TiO2@C obtained in this embodiment retains the layered structure of general MXene, but is more peeled off than the accordion structure, thus achieving the purpose of in-situ peeling.

[0035] Example 2

[0036] A method for controlled exfoliation and in-situ conversion of MXene, comprising the following steps:

[0037] a. Grind MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:6 in a mortar for 20 min to fully mix the powders and transfer them to a corundum crucible, wherein Ti3AlC2 is 2 g;

[0038] b. The crucible of step a was transferred to a tubular furnace, and the temperature was raised to 600°C at a heating rate of 5°C / min under an argon atmosphere, and kept at this temperature for 6 hours. After the end of the heat preservation, the temperature was first lowered to 200°C at a rate of 10°C / min, and then cooled with the furnace to obtain m-Ti3C2T z ;

[0039] c. The m-Ti3C2T obtained in step b z The mixture was mixed with a 2M weak oxidant ammonium persulfate solution at a ratio of 1 g:100 mL, and reacted at room temperature with magnetic stirring at 500 rpm for 8 h;

[0040] d. The solution obtained in step c was centrifuged at 8000 rpm for 3 min, and was centrifuged and washed twice with deionized water and anhydrous ethanol at 8000 rpm for 3 min each. The precipitate was collected and vacuum dried at 80° C. The powder was collected to obtain amorphous TiO2@C.

[0041] The specific surface area of ​​the amorphous TiO2@C obtained in this example is 141.6422 m 2 / g. The mass percentage of TiO2 is 32.64%, and the mass percentage of C is 67.36%.

[0042] like Figure 3 In the XRD spectrum of the amorphous TiO2@C obtained in this example, the small bulge at 20° to 30° corresponds to amorphous carbon, and there is no obvious diffraction peak in the figure, thus achieving the purpose of in-situ conversion of m-MXene.

[0043] like Figure 4 The amorphous TiO2@C obtained in this embodiment retains the layered structure of general MXene, but is more peeled off than the accordion structure, thus achieving the purpose of in-situ peeling.

[0044] Example 3

[0045] A method for controlled exfoliation and in-situ conversion of MXene, comprising the following steps:

[0046] a. Grind MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:5 in a mortar for 20 min to fully mix the powders and transfer them to a corundum crucible, wherein Ti3AlC2 is 2 g;

[0047] b. The crucible of step a was transferred to a tube furnace, and the temperature was raised to 660°C at a rate of 3°C / min under an argon atmosphere, and the temperature was kept for 5 hours. After the temperature was kept, the temperature was first lowered to 190°C at a rate of 8°C / min, and then cooled with the furnace to obtain m-Ti3C2T z ;

[0048] c. The m-Ti3C2T obtained in step b z The mixture was mixed with a 1M weak oxidant FeCl3 solution at a ratio of 2 g:100 mL, and reacted at room temperature with magnetic stirring at 600 rpm for 9 h;

[0049] d. Collect the product obtained in step c by suction filtration, collect the precipitate and freeze-dry it to obtain amorphous TiO2@C.

[0050] The specific surface area of ​​the amorphous TiO2@C obtained in this example is 130.7325 m 2 / g. The mass percentage of TiO2 is 34.63%, and the mass percentage of C is 65.37%.

[0051] Example 4

[0052] A method for controlled exfoliation and in-situ conversion of MXene, comprising the following steps:

[0053] a. Grind MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:7 in a mortar for 20 min to fully mix the powders and transfer them to a corundum crucible, wherein Ti3AlC2 is 2 g;

[0054] b. The crucible of step a was transferred to a tubular furnace, and the temperature was raised to 630°C at a heating rate of 3°C / min under an argon atmosphere, and the temperature was kept for 7 hours. After the temperature was kept, the temperature was first lowered to 195°C at a rate of 9°C / min, and then cooled with the furnace to obtain m-Ti3C2T z ;

[0055] c. The m-Ti3C2T obtained in step b z Mix with a weak oxidant ammonium persulfate solution or FeCl3 solution with a concentration of 0.5-2M at a ratio of 1.5 g:100 mL, and react with magnetic stirring at 550 rpm at room temperature for 8.5 hours;

[0056] d. The solution obtained in step c was centrifuged at 8000 rpm for 3 min, and was centrifuged and washed twice with deionized water and anhydrous ethanol at 8000 rpm for 3 min each, and the precipitate was collected and vacuum dried at 75° C. to obtain amorphous TiO2@C.

[0057] The specific surface area of ​​the amorphous TiO2@C obtained in this example is 159.2783 m 2 / g. The mass percentage of TiO2 is 31.95%, and the mass percentage of C is 68.05%.

[0058] Example 5

[0059] A method for controlled exfoliation and in-situ conversion of MXene, comprising the following steps:

[0060] a. Grind MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:5 in a mortar for 20 min to fully mix the powders and transfer them to a corundum crucible, wherein Ti3AlC2 is 2 g;

[0061] b. The crucible of step a was transferred to a tubular furnace, and the temperature was raised to 610°C at a heating rate of 4°C / min under an argon atmosphere, and the temperature was kept for 5 hours. After the temperature was kept, the temperature was first lowered to 198°C at a rate of 9°C / min, and then cooled with the furnace to obtain m-Ti3C2T z ;

[0062] c. The m-Ti3C2T obtained in step b z The mixture was mixed with a 2M weak oxidant ammonium persulfate solution at a ratio of 1 g:100 mL, and reacted at room temperature with magnetic stirring at 650 rpm for 9 h;

[0063] d. The solution obtained in step c was centrifuged at 8000 rpm for 3 min, and was centrifuged and washed twice with deionized water and anhydrous ethanol at 8000 rpm for 3 min each, and the precipitate was collected and dried naturally to obtain amorphous TiO2@C.

[0064] The specific surface area of ​​the amorphous TiO2@C obtained in this example is 146.3762 m 2 / g. The mass percentage of TiO2 is 33.62%, and the mass percentage of C is 66.38%.

[0065] Example 6

[0066] A method for controlled exfoliation and in-situ conversion of MXene, comprising the following steps:

[0067] a. Grind MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:7 in a mortar for 20 min to fully mix the powders and transfer them to a corundum crucible, wherein Ti3AlC2 is 2 g;

[0068] b. The crucible of step a was transferred to a tube furnace, and the temperature was raised to 650°C at a rate of 4°C / min under an argon atmosphere, and the temperature was kept for 7 hours. After the temperature was kept, the temperature was first lowered to 192°C at a rate of 8°C / min, and then cooled with the furnace to obtain m-Ti3C2T z ;

[0069] c. The m-Ti3C2T obtained in step b z The mixture was mixed with a 1M weak oxidant FeCl3 solution at a ratio of 2 g:100 mL, and reacted at room temperature with magnetic stirring at 580 rpm for 8.5 h;

[0070] d. The solution obtained in step c was centrifuged at 8000 rpm for 3 min, and was centrifuged and washed twice with deionized water and anhydrous ethanol at 8000 rpm for 3 min each. The precipitate was collected and vacuum dried at 85° C. to obtain amorphous TiO2@C.

[0071] The specific surface area of ​​the amorphous TiO2@C obtained in this example is 152.7394 m 2 / g. The mass percentage of TiO2 is 34.86%, and the mass percentage of C is 65.14%.

[0072] Among the above embodiments, the most preferred embodiment is Embodiment 1.

[0073] application

[0074] The amorphous TiO2@C obtained in Example 1 is used in the field of potassium storage, and the specific steps include: (1) amorphous TiO2@C is mixed with a conductive agent Super P and an adhesive CMC in a molar ratio of 7:2:1 and vacuum dried at 80°C for 12 hours to prepare a half-cell electrode; (2) the obtained electrode is assembled into a half-cell with a potassium sheet, an electrolyte and a glass fiber separator; (3) the assembled battery can stably operate for more than 4500 cycles at a current density of 0.5 A / g, and the specific capacity is maintained at about 110 mAh / g.

[0075] Comparative Example 1

[0076] The remaining steps of this comparative example are the same as those of Example 1, except that in step a, the molar ratio of Ti3AlC2 to CuBr2 is 1:4. It is found that the etching cannot be completed, and additional salt bed protection is required.

[0077] Comparative Example 2

[0078] The remaining steps of this comparative example are the same as those of Example 1, except that in step a, the molar ratio of Ti3AlC2 to CuBr2 is 1:8. It was found that subsequent copper removal was difficult.

[0079] Comparative Example 3

[0080] The remaining steps of this comparative example are the same as those of Example 1, except that in step c, the weak oxidant ammonium persulfate is replaced by silver ammonia solution. It is found that unnecessary impurities are introduced and difficult to remove, and the cost is too high.

Claims

1. A method for controlled exfoliation and in-situ conversion of MXene, characterized in that: The following steps are involved: Step 1: Grind and mix MAX phase Ti3AlC2 and CuBr2 in a molar ratio of 1:5-7 and transfer them into a container; Step 2: calcining the product obtained in step 1 at 600-660°C in a protective atmosphere, cooling it down and taking it out to obtain m-Ti3C2T z , where T z is the surface functional group Br; Step 3: m-Ti3C2T z Mix with weak oxidant in the ratio of 1~2g:100mL, and react under magnetic stirring at room temperature; Step 4, collecting and drying the product obtained in step 3 to obtain amorphous TiO2@C; In the step 3, the weak oxidant is ammonium persulfate solution or FeCl3 solution; the concentration of the weak oxidant is 0.5M~2M.

2. The method for controlled exfoliation and in-situ conversion of MXene according to claim 1, characterized in that: In the step 1, the container is a crucible.

3. The method for controlled exfoliation and in-situ conversion of MXene according to claim 1, characterized in that: In the step 2, the temperature is raised to 600-660° C. at a heating rate of 3-5° C. / min and kept at this temperature for 5-7 hours.

4. The method for controlled exfoliation and in-situ conversion of MXene according to claim 1, characterized in that: In the step 2, the temperature is firstly reduced to 190-200° C. at a rate of 8-10° C. / min, and then cooled in the furnace.

5. The method for controlled exfoliation and in-situ conversion of MXene according to claim 1, characterized in that: In the step 3, the rotation speed of the magnetic stirring is 500-700 rpm, and the time is 8-9 hours.

6. The method for controlled exfoliation and in-situ conversion of MXene according to claim 1, characterized in that: In the step 4, the collection is performed by centrifugation or filtration.

7. The method for controlled exfoliation and in-situ conversion of MXene according to claim 1, characterized in that: In the step 4, the drying is any one of vacuum drying, freeze drying and natural drying, and the temperature of the vacuum drying is 75-85°C.

8. The method for controlled exfoliation and in-situ conversion of MXene according to claim 1, characterized in that: The specific surface area of ​​the amorphous TiO2@C is 130~160m 2 / g.

Citation Information

Patent Citations

  • Few-layer TiO2-MXene composite material as well as preparation method and application thereof

    CN114883503A

  • A method for strengthening copper-based composite materials by utilizing the pinning effect between local in-situ oxidation of MXene and the matrix.

    CN115505781B

  • MXene material and preparation method and application thereof

    CN110540236A

  • Method for preparing MXenes material from molten salt

    CN112194135A